KEGAGALAN GOOD CORPORATE GOVERNANCE DALAM PERSPEKTIF TEORI KEAGENAN DAN ETIKA BISNIS PADA PT ASURANSI JIWASRAYA - Cintya Putri Nasution; Suaini Mebia Putri; Dia Aulia Harahap; Rian Afrijal (Adpertens: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the failure of Good Corporate Governance (GCG) implementation from the perspective of agency theory and business ethics at PT Asuransi Jiwasraya. This study uses a qualitative approach with a conceptual analysis method based on secondary data obtained from scientific journals, official reports, and relevant economic publications. The analysis results indicate that governance failure at PT Asuransi Jiwasraya is influenced by conflicts of interest between management and stakeholders, information asymmetry, moral hazard, and weak internal controls. Furthermore, the practice of non-transparent information presentation and imprudent investment decisions indicate that ethical business values ​​have not been optimally internalized in the company's decision-making process. These findings confirm that the application of the principles of transparency, accountability, responsibility, independence, and fairness has not been implemented substantively but rather tends to be formalistic. This failure not only impacts financial losses but also undermines public trust in the insurance industry. Therefore, this study demonstrates that successful GCG requires the integration of structural compliance, effective oversight, and the internalization of business ethics as the foundation of company operations.